Exploration of Risk Attitude of Vegetable Farmers in Kerala, India - Raj, Navitha; Thomas, Allan (International Journal of Bio-resource and Stress Management, 2022)
The study was conducted in Alappuzha, Thrissur, Palakkad and Idukki districts of Kerala, India during 2020–2021 to analyse the risk attitude of vegetable farmers. The study examined the personal and social characteristics of respondents and the association of these characteristics with risk attitude. Simple random sampling technique was used to select 270 vegetable farmers from 6 panchayats representing the Special Agricultural Zones for vegetables in Kerala. Collected data were analyzed using statistical methods like mean, Kruskal-Wallis test, correlation coefficient and multiple regressions. The study revealed that majority (74.07%) of the farmers belonged to a medium category of risk attitude. Majority (55.18%) of the farmers were in the age group of 35−55 years, 46.29% had gone up to middle school, 72.59% of the farmers had an area below 2.31 acres and 67.4% respondents were engaged in vegetable farming and allied works and 54.07% had economic water scarcity. It was noticed that majority of the respondents were in the low category in the case of vegetable farming experience (61.48%), annual income (55.56%), innovative proneness (56.67%), economic motivation (56.3%), extension participation (70%), social participation (94.44%) and high category with regard to credit orientation (53.7%). Correlation analysis revealed that variables area under vegetable cultivation, education, annual income, irrigation potential, extension participation, innovative proneness, economic motivation and social participation were positively and significantly corelated with risk attitude of respondents at 1% level and at 5% level. Regression analysis revealed that 60% of the variation in farmer risk attitude was explained by the independent variables.